sinA+cosA/sinA-cosA + sinA-cosA/SinA+cosA=1/sin^2A-cos^2=2/1-2cos^2A=2sec^2A/tan^2A-1
Answers
Answered by
34
if it helps u
Mark BRAINLIEST thank u
Mark BRAINLIEST thank u
Attachments:
![](https://hi-static.z-dn.net/files/d29/7c62c6c848d40968d85460223fa56960.jpg)
Answered by
5
________________________
We know that,
- 1) (a+b)² + (a-b)² = 2(a²+b²)
- 2)(a-b)(a+b) = a² - b²
- 3) sin²A + cos²A = 1
________________________
/* Dividing numerator and denominator by cos² A , we get */
•••♪
Similar questions